GIS-material for the archaeological project: Bogestad-Harvestad-Edsberga - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to the laying of cable, changing of transformer stations and installation of electrical link boxes between Bogestad and Nain, the Swedish National Heritage Board's contract archaeology division, UV Öst, performed a preliminary investigation in September 2005 along the distance Bogestad-Harvestad-Edsberga-Nain, in Landeryd parish, Linköping municipality. The investigation was performed as an antiquarian inspection and was conducted within four sections, where the cable was being laid nearby known archaeological sites. Section 1 ran along the settlement and burial area RAÄ 287. No archaeological remains were affected. Section 2 went along Högsbacken with the burial ground RAÄ 12. No prehistoric remains were discovered. Section 4 extended to the top of the site of the medieval village Edsberga, RAÄ 318. North-east of the village site is as Iron Age settlement, RAÄ 63. The cable was here planned to be laid in an existing trench, and no remains were thus affected. Section 5 ran over the top of a ridge and between two areas of waste land, close by the croft remnant RAÄ 319. Except for a pit with brown-gray soil and a shard of pottery, no artefacts or features were found. UV Öst concludes that the cable can be laid without any further archaeological measures being taken.

Purpose:

The information in the abstract is translated from the archaeological report:
The purpose of the antiquarian inspection was to determine whether any archaeological remains were going to be affected by the earthworks.

The ZIP file consist of GIS files with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst utförde under september 2005 en arkeologisk förundersökning i form av antikvarisk kontroll längs med sträckan Bogestad-Harvestad-Edsberga-Nain, i Landeryds socken, Linköpings kommun. Förundersökningen föranleddes av en planerad förläggning av jordkabel samt byten av marktransformatorstationer och installering av kabelskåp mellan Bogestad och Nain. Dessutom planerades rasering av befintlig luftledning mellan Edsberga-Nain- Norrberga, Landeryds och Vists socknar. Antikvarisk kontroll skulle utföras inom fyra sträckor där jordkabel skulle förläggas i anslutning till kända fornlämningar. Rasering av befintlig luftledning bedömdes inte beröra några fasta fornlämningar.
Sträcka 1 löpte intill grav- och boplatsområde RAÄ 287. Inga fornlämningar kom här att beröras. Sträcka 2 följde längs med Högsbacken med järnåldersgravfältet RAÄ 12. Inga förhistoriska lämningar kunde konstateras. Sträcka 4 ledde upp till krönläget av den medeltida bytomten Edsberga, RAÄ 318. Nordöst om bytomten finns även en järnåldersboplats, RAÄ 63. Den planerade jordkabeln skulle här läggas i befintligt ledningsschakt, varför arbetsföretaget inte kom att beröra några fornlämningar. Sträcka 5 ledde över en höjdrygg och ett sadelläge mellan två impediment intill torplämning RAÄ 319. Utöver en grop med brungrå fyllning och en rödgodsskärva påträffades inga fynd eller lämningar. UV Öst anser efter utförd undersökning att jordkabeln kan förläggas utan vidare antikvariska åtgärder inom de berörda sträckorna.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den antikvariska kontrollen var att klargöra om arkeologiska lämningar påverkades av markarbetena.

ZIP-filen innehåller GIS-filer med information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Bogestad-Harvestad-Edsberga
Keywords: HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive